Maturity Models for Digitalization in Manufacturing - Applicability for SMEs - Wiesner, Stefan; Gaiardelli, Paolo; Gritti, Nicola; Oberti, Gianluca (Advances in Production Management Systems. Smart Manufacturing for Industry 4. 0, 2018)
Digitalization is a challenging topic for manufacturing SMEs. Besides improving their technological base, they have to keep the business offer attractive, e.g. by bundling their products with smart services. In addition to limited resources, often the necessary knowledge is missing to select the right technologies and develop attractive services based on their functionality. Due to the resulting high risks, SMEs neglect the chances of digitization and lose competitiveness. To start with, they need a maturity assessment model that can help them understand their level of readiness to implement aspects, such as Industry 4.0. In order to identify and fit such a model for SMEs, already existing assessment methods were analyzed according to a series of selected dimensions linked to SMEs features. The evaluation result illustrates requirements that have to be addressed by a new maturity model suitable for SMEs attempting digitalization.